Pengaruh Sistem Pengendalian Internal Pemerintah (SPIP), Kompetensi Sumber Daya Manusia, dan Moralitas Terhadap Pencegahan Kecurangan (Fraud) Pada Inspektorat Kota Bandung - Sarah Affifah Aprilianty; Kartika Berliani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The rapid development of accounting today not only provides a positive contribution in increasing the transparency and accountability of financial reports, but also creates new risks, one of which is the increased potential for fraud. Recognizing the importance of this issue, this study was conducted to examine the factors that influence fraud prevention. Using quantitative research with descriptive and verification approaches. The data were collected through library research, field research, interviews & questionnaires to 64 respondents who were all auditors of the Bandung City Inspectorate. The sampling technique used a non-probability sampling technique with a total sampling approach, meaning the entire research population was sampled. Data analysis was carried out with the help of SPSS version 26 through a series of tests, including validity, reliability, classical assumptions, and hypothesis testing. The results show that SPIP and HR Competence have a significant impact on fraud prevention, in contrast to Morality which has no significant effect. The R-Square value obtained was 0.906 or 90.6%, which means that the independent variables play a dominant role in influencing fraud prevention, although the remaining 9.4% is influenced by external factors outside the scope of this study.